EFL teachers’ oral interaction enhancement through cooperative learning worksheets (2021)
This qualitative action research study spotlighted the implementation of worksheets developed by the teacherresearcher and based on cooperative learning techniques to enhance in-service EFL teachers’ oral interaction. The research study was carried out with a group of ten inservice EFL teachers in a non-formal public institution in Cundinamarca. The grounded theory approach supported the analysis of data gathered through artefacts, field notes, and video and audio recordings. It is found that the use of appealing topics in materials can increase in-service EFL teachers’ oral communication. Moreover, the incorporation of learning strategies in the materials promoted interaction in this group of teachers. Consequently, cooperative learning helped them to overcome linguistic difficulties. In the same way, cooperative learning created a favourable class atmosphere that fostered participation. In relation to oral interaction, the participants used some strategies to communicate accurately and defined some roles while interacting. It is also acknowledged that contextualised EFL materials generated by the teacher-researcher boosted students’ motivation in in-service teachers’ realities, countered conventional content and learning activities included in standardised EFL textbooks and foster the teacher-researcher’ personal and professional growth.